2023
DOI: 10.1101/2023.03.30.23287976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive Intervention Effects Vary as a Function of Plasma Neurofilament Light Chain Levels: A PICMOR Randomized Controlled Trial

Abstract: Background: There is a difference in the neuronal state of individuals. However, this has not been taken into consideration in most intervention studies. Recent advances in analytical technologies in hematological examination enabled us to evaluate neuronal states in a relatively convenient manner. Objective: Using these advanced technologies, we aimed to investigate whether cognitive intervention effects vary as a function of levels of blood-based biomarkers, such as neurofilament light chain (NfL), since pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This study has some strengths. One strength is that we presented a technical framework for examining the impact of “asking questions,” an important factor for conversation-based interventions for cognitive function, which was lacking in our previous studies [ 17 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has some strengths. One strength is that we presented a technical framework for examining the impact of “asking questions,” an important factor for conversation-based interventions for cognitive function, which was lacking in our previous studies [ 17 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Another strength of this study is that we successfully conducted home-based interventions while most intervention studies, including our previous ones [ 17 21 ], have been conducted on-site. Notably, this study demonstrated that home-based interventions are feasible even though some participants were unfamiliar with digital devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main outcome measure is cognitive function. Specifically, we hypothesized that the PICMOA may stimulate linguistic and executive functions through fundamental conversation activities based on the results of previous RCTs [22,23,27] and mechanistic hypothesis based on the explanatory investigation using multimodal MRI [24][25][26]. Thus, we will specifically focus on verbal fluency as the primary outcome, which may reflect linguistic and executive functions.…”
Section: Cognitive Functionsmentioning
confidence: 99%
“…Based on the above evidence, we hypothesized that social communication-based interventions would be effective in maintaining cognitive function. Consequently, a series of our previous RCTs examined the effect of structural face-to-face group conversation intervention and consistently observed some positive effects on verbal fluency [22,23]. Our explanatory investigation using multimodal magnetic resonance imaging (MRI) identified the brain network, brain regions, and brain structure that could benefit from the intervention.…”
Section: Introductionmentioning
confidence: 96%